MODERATISME FIKIH PEREMPUAN YUSUF AL-QARDHAWI - Ma'mur, Jamal (MUWAZAH, 2016)
This paper examines the thought Yusuf al-Qardhawi about women fiqh. The theory used is maqasidus Shari'ah. The analysis used was content analysis. This research, including qualitative research because examines the idea of a character in response to public issues are very real. The results showed that, women in the time of Prophet Muhammad followed the prayer jamaah, Jum'ah prayer, the prayer of Eid fithri and Eid al-Adha.They also attended the majlis of science and even in the battlefield. Women are also allowed to work outside the home with requirements pertaining to religion and are not prohibited, consistently maintaining the ethics of Islam, and not leave its core responsibilities to her husband and children. in the context of the public, women should be leaders;and others.paper ini mengkaji pemikiran Yusuf al-Qardhawi tentang fiqh perempuan. Teori yang digunakan adalah maqasidus syari’ah (tujuan aplikasi hukum syariat). Analisis menggunakan content analysis. Penelitian termasuk penelitian kualitatif karena mengkaji gagasan seorang tokoh dalam merespons isu-isu publik yang aktual. Hasil penelitian menunjukan, bahwa perempuan masa Nabi mengikuti shalat jama’ah, shalat jum’ah, shalat idul fithri dan idul adha. Mereka juga, menghadiri majlis ilmu dan berada di medan perang. Perempuan juga boleh bekerja di luar rumah dengan syarat profesinya dibolehkan agama dan tidak diharamkan, konsisten menjaga etika Islam, dan tidak meninggalkan kewajiban utamanya kepada suami dan anak-anak; dalam konteks publik, perempuan boleh menjadi pemimpin; dan lain-lain.